2015
DOI: 10.1002/stem.2086
|View full text |Cite
|
Sign up to set email alerts
|

The Corepressor Rcor1 Is Essential for Normal Myeloerythroid Lineage Differentiation

Abstract: Based on its physical interactions with histone-modifying enzymes, the transcriptional corepressor Rcor1 has been implicated in the epigenetic regulation blood cell development. Previously, we have demonstrated that Rcor1 is essential for the maturation of definitive erythroid cells and fetal survival. To determine the functional role of Rcor1 in steady-state hematopoiesis in the adult, we used a conditional knockout approach. Here, we show that the loss of Rcor1 expression results in the rapid onset of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…To explore other potential functional partners of MED28, we predicted its potential partners with direct bindings (Figure 3A). Among the candidates, we noticed that RCOR1 is a stem cell differentiation‐related protein 11,12 . Interestingly, RCOR1 expression was significantly higher in SCC9/CD44 low cells than in SCC9/CD44 high cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To explore other potential functional partners of MED28, we predicted its potential partners with direct bindings (Figure 3A). Among the candidates, we noticed that RCOR1 is a stem cell differentiation‐related protein 11,12 . Interestingly, RCOR1 expression was significantly higher in SCC9/CD44 low cells than in SCC9/CD44 high cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 96%
“…Thus, we further explored the functional partner of MED28 in OCSCC. Among the predicted partners, RCOR1 is a modulator of stem cell differentiation, which induces mouse embryonic stem cell differentiation 11 and normal myeloerythroid lineage differentiation 12 . We demonstrated that RCOR1 could suppress the CSC‐like properties of SCC9 cells and had direct interaction with MED28.…”
Section: Discussionmentioning
confidence: 91%
“…Rcor1 also recruits the INSM1/Rcor1/2 complex, controlling the balance of proliferation and differentiation during brain development (20). In hematopoietic stem cells, loss of Rcor1 in adults leads to a complete block in erythroid and neutrophil differentiation (21). Although Rcor1 functions as an epigenetic and repressive factor in immune cells, its role in the regulation of Foxp3 + Tregs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported as an essential factor in normal differentiation of myeloerythroid progenitors, which regulates self-renewal activity in monocytes. 85 , 86 More studies should be done on RCOR1 expression in leukemia patients in order to determine its role in malignant hematopoiesis.…”
Section: Mir-9 and Cell Cyclementioning
confidence: 99%